2018
DOI: 10.3390/su10061775
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Irrigation and Drainage Management to Sustain Agriculture in Northern Iran

Abstract: In Iran, as in the rest of the world, land and water for agricultural production is under pressure. Integrating irrigation and drainage management may help sustain intensified agriculture in irrigated paddy fields. This study was aimed to investigate the long-term effects of such management strategies in a newly subsurface drained paddy field in a pilot area in Mazandaran Province, northern Iran. Three strategies for managing subsurface drainage systems were tested, i.e., free drainage (FD), midseason drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…DRAINMOD slightly underestimated daily drain flows in D0.65L15. In heavy‐textured soils, installation of shallow drains at narrow spacing provides suitable conditions for formation of cracks and preferential flow occurs due to wetting and drying of the soil (Darzi‐Naftchali and Ritzema, 2018) which could not be simulated by the model.…”
Section: Resultsmentioning
confidence: 99%
“…DRAINMOD slightly underestimated daily drain flows in D0.65L15. In heavy‐textured soils, installation of shallow drains at narrow spacing provides suitable conditions for formation of cracks and preferential flow occurs due to wetting and drying of the soil (Darzi‐Naftchali and Ritzema, 2018) which could not be simulated by the model.…”
Section: Resultsmentioning
confidence: 99%
“…Agricultural drainage facilities are installed to manage the production of crops through water supply and drainage. Flow-rate control, cultivation methods and drainage systems were studied in various ways to improve crop production [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In spite of these efforts, if crops are flooded because of overflow damage due to the accumulation of debris in agricultural drainage, a huge amount of production is damaged.…”
Section: Discussionmentioning
confidence: 99%
“…To provide continuous water supply in agricultural areas, it set up agricultural drainage for groundwater flow rate and suggested a plan for control and management [8][9][10][11][12][13][14][15]. It was explained that the efficiency of water use through the installation of agricultural drainage has an effect on harvesting by diversifying crops and reducing costs [16,17]. In addition, historical reviews of drainage channels in agriculture as well as methods of utilization based on ancient hydraulic technology were proposed [18].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study on paddy fields in China found that reducing drainage depth resulted in a drainage flow reduction of 50-60%, but no clear trend was observed in N concentration changes in drainage water (Luo et al 2008). In a field study in Iran, Darzi-Naftchali and Ritzema (2018) concluded that managed drainage can reduce N losses in drainage water and improve paddy rice yields compared with conventional drainage.…”
Section: Introductionmentioning
confidence: 95%